ANALISIS PENGARUH PERGANTIAN KANTOR AKUNTAN PUBLIK TERHADAP LIKUIDITAS SAHAM (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2014) - Desita Nurwigati; Paulus Th Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2016)
This research aims to investigate the influence of auditor switching as independence and stock liquidity  as  dependence  variables.  First  investigation,  it  examines  the  influences  of  auditor switching on stock liquidity. Secondly, it analyzes the difference in influences between voluntary auditor switching and mandatory auditor switching on stock liquidity. This study used secondary data. The population consists of manufacture   firms listed on the Indonesia Stock Exchange. Sampling method used in this study is purposive sampling and obtained 167 observations. Multiple regression analysis used to be analysis technique. The results of this study show that auditor switchces  had  positively  significant  influence  on  stock  liquidity.  while,  mandatory  auditor switching and voluntary auditor switching have no difference influenced on stock liquidity.